فاعلية استخدام التعلم المعكوس في تدريس العلوم في اكتساب المفاهيم العلمية وعمليات العلم الأساسية لدى طلاب الصف الثامن الأساسي في الأردن - الحراحشة، كوثر عبود موسى (الجامعة الأردنية - عمادة البحث العلمي, 2019)
This Study investigates the effect of using flipped learning on Acquiring of scientific concepts and Basic Science processes skills among eighth graders as compared to using traditional methods. The study sample consisted of (62) Male eighth graders chosen purposefully from Rehab Basic School for Boys in Mafraq center Educational Directorate. This sample was divided randomly into two groups: The experimental group consisting of (30) male students who were taught using Flipped learning. The control group consisting of (32) male students who were taught using traditional methods. To achieve the aims of the study, the researcher prepared an Acquiring of scientific concepts test including (25) multiple choice items in its final version and an instructional guide for teaching scientific concepts. Researcher also prepared a test to measure science processes skills. The study revealed the following results: There was a statistically significant difference between the means of the two groups for both the Acquiring of scientific concepts test and science processes skills test in favor of the experimental group.
هدفت هذه الدراسة استقصاء فعالية استخدام التعلم المعكوس في اكتساب المفاهيم العلمية في العلوم، ومهارات عمليات العلم الأساسية لدى طلاب الصف الثامن الأساسي في مادة العلوم العامة، مقارنة بالطريقة الاعتيادية. وتكونت عينة الدراسة من (62) طالبا تم اختيارهم بطريقة قصدية من طلاب الصف الثامن الأساسي من مدرسة رحاب الأساسية للبنين التابعة لمديرية قصبة المفرق في الأردن، مقسمة إلى شعبتين وزعت عشوائيا إلى مجموعتين: مجموعة تجريبية تكونت من (30) طالبا درسوا باستخدام التعلم المعكوس، ومجموعة ضابطة تكونت من (32) طالبا درسوا باستخدام الطريقة الاعتيادية. ولتحقيق أهداف الدراسة قامت الباحثة بإعداد اختبار اكتساب المفاهيم العلمية مكون من (25) فقرة من نوع الاختيار من متعدد بأربعة بدائل، وإعداد دليل تعليمي لتدريس المفاهيم العلمية باستخدام التعلم المعكوس، وأيضا قامت الباحثة بإعداد اختبار لعمليات العلم الأساسية. وأظهرت نتائج الدراسة فرقا دالا إحصائيا بين متوسطي علامات الطلاب في مجموعتي الدراسة على اختبار اكتساب المفاهيم العلمية واختبار عمليات العلم لصالح الطلاب الذين درسوا باستخدام التعلم المعكوس مقارنة بزملائهم الذين درسوا بالطريقة الاعتيادية.
Keywords: التعلم المعكوس -- الأردن -- مادة العلوم -- المفاهيم العلمية